The movie musical - Garcia, Desirée J., 1977- (Quick takes: movies and popular culture, 2021)
"With the release of each new musical film, critics ask, "Has the musical returned?" The very frequency of the question would seem to belie its implication. Indeed, while musicals have changed over time, they have never truly gone away. This point becomes especially clear if we look beyond the "golden age" of the 1940s and 50s, beyond Hollywood, and even beyond the United States. The Movie Musical is a thematic exploration of the genre with a focus on how the musical changes and adapts in order to preserve its own relevance. From The Jazz Singer (1927), The Sound of Music (1965) to La La Land (2016) and The Greatest Showman (2017) and many more, the book traverses time and space, from the classical period of musical film production at midcentury to the present, and from Hollywood to Europe, the United Kingdom, and Asia. Chapters explore the genre as an archive of its own formation, its engagement with race, ethnicity, and gender, and its relationship to ever evolving technologies and media. Ultimately, the book tells a story of the musical's evolution that denies the familiar narrative that the genre is in crisis; instead, The Movie Musical demonstrates that, if we look beyond the familiar places, we see that the musical is dynamic, capacious, and always with us"--